2018
DOI: 10.1016/j.envint.2018.05.045
|View full text |Cite
|
Sign up to set email alerts
|

Nickel and associated metals in New Caledonia: Exposure levels and their determinants

Abstract: The ultramafic massifs of the New Caledonian archipelago contain about 10% of the world's nickel reserves, which also contain significant but lower amounts of cobalt, chromium, and manganese. Natural erosion of these massifs and mining activities may contribute to the exposure of local populations to these metals through contamination of air, food, and water resources. We conducted a biomonitoring survey to evaluate exposure to these four metals and its main determinants by constructing a stratified sample of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…These unique differences reflect local anthropogenic activities adjacent to the sampled residential environments, including the production, use, and burning of Cu−Cr− As treated timber in New Zealand 79 and geology and industry in New Caledonia. 80,81 Cumulative exposure to trace metals has been significantly associated with health impacts such as obesity, hypertension, and type-2 diabetes. 82 Cao 83 reports that cumulative risks for children's trace metal exposures must be considered, rather than simply considering each trace metal individually.…”
Section: Resultsmentioning
confidence: 99%
“…These unique differences reflect local anthropogenic activities adjacent to the sampled residential environments, including the production, use, and burning of Cu−Cr− As treated timber in New Zealand 79 and geology and industry in New Caledonia. 80,81 Cumulative exposure to trace metals has been significantly associated with health impacts such as obesity, hypertension, and type-2 diabetes. 82 Cao 83 reports that cumulative risks for children's trace metal exposures must be considered, rather than simply considering each trace metal individually.…”
Section: Resultsmentioning
confidence: 99%
“…A study on Australian test species in field‐collected natural waters from Australia (Peters et al 2018 ) concluded that the existing approaches for normalization of ecotoxicity data to local water chemistry conditions (e.g., Nys et al 2016 ) were also appropriate for tropical species. Additionally, ongoing work in New Caledonia focuses on the development of an EQS in a region defined by high background Ni concentrations in fresh waters (e.g., tap water concentrations in the order of 10 µg/L; St‐Jean et al 2018 ). The New Caledonia EQS project consists of a multistep approach and includes not only quantifying the background Ni concentrations but also expanding to selecting tests for waters with a wide range of bioavailability potentials of Ni, identifying and isolating native species for testing, and ultimately performing toxicity tests to generate reliable toxicity threshold values applicable to the area.…”
Section: Methodsmentioning
confidence: 99%
“…Anthropic activities such as openpit mining and the natural erosion of soils in New Caledonia has led to the atmospheric emission of Ni particles and, in particular, to the emission of nickel oxide nanoparticles (NiONPs) due to the hydrometallurgical process used to extract Ni [8,9]. Previous studies have revealed significant contamination levels in the New Caledonian population and have shown elevated levels of Ni in the lungs of nickel refinery workers [10,11]. Moreover, cardiovascular diseases were found to be more prevalent among those workers [12].…”
Section: Introductionmentioning
confidence: 99%